Illegal Parking Control Strategy to Improve Sustainable Management of Urban Areas - Erfina Erfina; Lukman Lukman; Hardianti Hardianti; Balázs Benjámin Budai (Journal of Governance and Public Policy, 2025)
Illegal parking in Sidenreng Rappang Regency has significant implications for spatial planning, traffic management, and public space utilization, negatively affecting the quality of life, accessibility, and local businesses. This study investigates strategic solutions to address this issue using a qualitative approach, incorporating in-depth interviews, focus group discussions, field observations, and document analysis. Data were analyzed using the SWOT framework and NVivo software, revealing that weak regulatory enforcement and inadequate infrastructure are the primary drivers of illegal parking. However, opportunities exist in the form of smart parking technologies, public-private partnerships, and sustainable urban development initiatives. The novelty of this study lies in its integration of qualitative analysis with advanced digital tools, such as NVivo software, to provide a structured, data-driven approach to addressing governance challenges in urban mobility. This combination enables a more nuanced understanding of the problem and facilitates the development of targeted, evidence-based solutions. Additionally, the study introduces innovative strategies, such as the integration of digital technologies (e.g., CCTV and mobile parking applications) and the promotion of public-private partnerships, to create sustainable parking management systems. The study proposes actionable strategies, including strengthening regulatory enforcement, expanding parking infrastructure, integrating digital technologies, and launching public awareness campaigns. This research contributes valuable insights to urban planning and governance literature, providing a potential model for other regions facing similar challenges. It underscores the importance of integrating technological advancements and community engagement in creating effective, long-term solutions to urban mobility issues, ultimately enhancing the quality of life and economic vitality in affected areas. The novelty of this approach combining qualitative methods with digital tools and innovative strategies positions it as a pioneering effort in addressing illegal parking and urban governance challenges.